Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1182/blood.v118.21.4060.4060
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Risk-Based Algorithm for the Utilization of Plerixafor As Primary Mobilization of CD34+ Cells in Autologous Hematopoietic Cell Transplant Candidates,

Abstract: 4060 Study Purpose and Methods: Following FDA approval of plerixafor, our institution developed practice guidelines using a risk-based algorithm to optimize the use of plerixafor for CD34 cell mobilization in autologous hematopoietic cell transplant (HCT) candidates. We defined patients (pts) at high risk for mobilization failure and eligible to receive G-CSF 10 mcg/kg/day for 4 days with plerixafor 0.24 mg/kg added on day 4 if they met any of the following criteria: 1) 3 or more lines of prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In a phase II trial, the addition of plerixafor to G-CSF mobilization increased rates of successful mobilization (defined as !5 Â 10 6 CD34 þ cells/kg) and was associated with fewer apheresis sessions compared with G-CSF alone [129]. Two subsequent large Phase III trials of upfront plerixafor þ G-CSF (P þ G-CSF) mobilization confirmed that the combination was associated with higher CD34 þ cell yields, better achievement of collection targets, lower failure rates, and fewer apheresis sessions compared with G-CSF alone [66,67,[130][131][132][133].…”
Section: Upfront Mobilizationmentioning
confidence: 99%
See 3 more Smart Citations
“…In a phase II trial, the addition of plerixafor to G-CSF mobilization increased rates of successful mobilization (defined as !5 Â 10 6 CD34 þ cells/kg) and was associated with fewer apheresis sessions compared with G-CSF alone [129]. Two subsequent large Phase III trials of upfront plerixafor þ G-CSF (P þ G-CSF) mobilization confirmed that the combination was associated with higher CD34 þ cell yields, better achievement of collection targets, lower failure rates, and fewer apheresis sessions compared with G-CSF alone [66,67,[130][131][132][133].…”
Section: Upfront Mobilizationmentioning
confidence: 99%
“…Plerixafor also has been used in risk-adapted strategies in which patients with high-risk baseline characteristics are mobilized with P þ G-CSF. One single-center report of P þ G-CSF use in patients at high risk for mobilization failure based on previous chemotherapy regimens showed significantly improved mobilization compared with historical controls who received G-CSF alone [133]. Another retrospective study of P þ G-CSF in patients at high risk for failure based on medical history found a failure rate of only 4%; however, it should be noted that one-third of the patients in this cohort had previously failed mobilization [131].…”
Section: Preemptive and Risk-adapted Plerixafor Usementioning
confidence: 99%
See 2 more Smart Citations
“…Plerixafor is indicated for first-line mobilization of hematopoietic stem cells into the peripheral blood for collection and subsequent autologous transplantation in patients with NHL and MM. Several studies, including the initial phase III trials of plerixafor and G-CSF compared with G-CSF and placebo, have demonstrated that plerixafor can overcome some of the known risk factors for poor stem cell mobilization [26,43,[59][60][61], and may reduce overall mobilization failure rates from as high as 30% to <10% [16,21,[62][63][64][65][66][67][68]. Unfortunately, the acquisition cost of plerixafor has limited its use in up-front mobilization despite the FDA indication, as expensive agents within institutions are often restricted because of budget constraints.…”
Section: Novel Mobilization Approachesmentioning
confidence: 99%